2010
DOI: 10.1111/j.1399-5618.2010.00876.x
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation between bipolar disorder and schizophrenia revealed by neural oscillation to speech sounds: an MEG study

Abstract: The present study showed that different patterns in eNO to speech sounds are present in BP, SZ, and NC subjects. The eNO to speech sounds in the left hemisphere is a potential index to distinguish BP and SZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Significant differences in gamma-band power in schizophrenia have been observed in a number of paradigms, but reports of decreases in gamma-band power in SP are more common than increases (for a review, see Sun et al, 2011). It is important to note that some of these studies limited their analysis to specific regions of interest (e.g., Teale et al, 2008; Oribe et al, 2010), thereby limiting the scope of the study to the region analyzed. Our analysis limited the frequency range to the low gamma-band, yet performed comparisons across the full sensor array providing a broader view of changes in gamma-band power.…”
Section: Discussionmentioning
confidence: 99%
“…Significant differences in gamma-band power in schizophrenia have been observed in a number of paradigms, but reports of decreases in gamma-band power in SP are more common than increases (for a review, see Sun et al, 2011). It is important to note that some of these studies limited their analysis to specific regions of interest (e.g., Teale et al, 2008; Oribe et al, 2010), thereby limiting the scope of the study to the region analyzed. Our analysis limited the frequency range to the low gamma-band, yet performed comparisons across the full sensor array providing a broader view of changes in gamma-band power.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, two meta-analyses of volumetric studies of superior temporal cortices did not report any significant differences between patients with bipolar disorder and healthy participants (Arnone et al, 2009; Kempton et al, 2008). However, primary and secondary auditory cortices are located in the region and functional studies consistently reported auditory processing disturbances in both schizophrenia (Dierks et al, 1999; Domjan et al, 2012; Umbricht and Krljes, 2005) and bipolar disorder (Hall et al, 2009; Oribe et al, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…Since glutamate is the major excitatory neurotransmitter and since the EEG signal consists of excitatory end synaptic potentials, auditory processing deficits detected in both schizophrenia (Oribe et al, 2010; Umbricht and Krljes, 2005) and bipolar disorder (Atagun et al, 2014; Ethridge et al, 2012; Hall et al, 2009) could potentially be due to glutamatergic dysfunction in the auditory cortices (Javitt, 2009). Glutamate-modulating agents have been found to be efficacious in the treatment of mood disorders both in pre-clinical (Skolnick et al, 2009) and clinical studies (Machado-Vieira et al, 2012; Sanacora et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that while neurophysiological responses to vowel sounds are lateralized, those to nonspeech sounds are not [9,10,11,12]. Clinically, it has been reported that these lateralized early neural responses to vowel sounds are disturbed in psychotic patients [13,14,15]. Moreover, abnormalities of the perceptual process in the audiovisual integration stimuli have been reported in schizophrenia [16].…”
Section: Introductionmentioning
confidence: 99%